Fever and School Attendance among Basic School Children in Adentan Municipality - Appiah, D.N. (University of Ghana, 2016)
Introduction: Fever is a common presentation in children and oftentimes, it is a predictive marker for an underlying infection. School attendance plays an important role in a child’s personal, social and academic development. It is estimated that, in Ghana, only 58% of children who enrol in class one make it to class six and in Adentan municipality, 27.3% of children have dropped out of school, which is a long – term consequence of school non – attendance and probably as a result of fever and fever – related diseases. The relationship between school attendance and fever has not been studied in any urban setting, despite the fact that non – attendance continues to be on the rise. Therefore the study seeks to determine the relationship between fever and school attendance among basic school children and to quantify this relationship. Method: The study used a descriptive cross – sectional study to determine the prevalence of fever among basic school children, the contributing factors and the rates of school non – attendance due to fever among this group. A bivariate analysis test was fitted to examine the factors that influenced the occurrence of fever in the two weeks preceding the study and also used to determine the factors that contributed to school non – attendance among the basic school children. Results: Prevalence of fever among basic school children was 57.97% and was affected significantly by disease occurrence among them which proved to be the single most important risk factor for fever. School attendance was influenced by age, socioeconomic status, zone of child’s residence and lack of water as well as their attendance rates due to fever. School non – attendance rates due to fever was calculated to be 53.6% per term indicating that more than half of all school absences is caused by fever. Conclusion: There was no direct relationship between occurrence of fever among basic school children in the two weeks preceding the study and school attendance.
Thesis(MPH)-University of Ghana, 2016
Keywords: Fever; School Attendance; Basic School Children